THE INFLUENCE OF MOTIVATION AND COMMUNICATION QUALITY ON EMPLOYEE PRODUCTIVITY AT PT. PLN (Persero) SECTOR TELLO MAKASSAR - Usman; H Djabir Hamzah; Sumardi (Scientium Management Review, 2023)
This research aims toanalyze the influence of motivation and quality of communication on employee productivity at PT PLN (Persero) Sector Tello Makassar.This research was conducted using a quantitative approach and a survey.The population consists of all employees of PTPLN (Persero) Tello Sector in Makassartotaling 134 people with the sampling method in this study using the full sample method. The results showed that (1) motivation is the most influential variable on employee productivity because it has the largest correlation coefficient value. This means that the increase in employee productivity is highly dependent on the motivation that underlies or encourages employees to work and (2) the quality of communication has a significant effect on productivity which indicates that employees who have high perceptions of the quality of communication tend to establish good relationships and create close communication. and harmony among fellow employees so as to increase productivity.